Analysis of the Natuna Islands Conflict between Indonesia and China in the Perspective of International Law - Shafira Nazhimah; Shavira Ardita Maharani; Clarissa Mayella Chandra; Ahmad Sudiro; Lewiandy Lewiandy (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This article aims to analyze the dispute between Indonesia and China regarding the Natuna Islands from an international law perspective. As a maritime country with many islands, Indonesia has abundant natural wealth in its territory. However, Indonesia and China's conflicting claims over the Natuna Islands have created tensions and disputes between the two countries. The dispute is related to the ownership and utilization of resources on Natuna Island which is in the Indonesian Exclusive Economic Zone. The impact of this dispute includes economic instability, divisions between countries, political losses, and social problems. In dealing with these impacts, it is necessary to carry out effective resolution efforts. Settlement of the Natuna islands dispute between Indonesia and China can be done through several strategic steps. First, regional border management is improved, economic activity is improved by exploring for oil in the Natuna Islands, then through an international legal approach, this article will review the relevant legal basis, legal arguments used by both parties, as well as possible settlement efforts.